Programming a Variety of Gains Is Possible by Controlling Intake of a Single High-Energy By-Product-Based Diet Early in the Receiving/Growing Period Without Affecting Efficiency - T. J. Spore; S. P. Montgomery; E. C. Titgemeyer; G. A. Hanzlicek; Christopher Vahl; T. G. Nagaraja; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:Analyze the effects on performance when feeding a high-energy by-product-based diet to newly received growing cattle. Description:A total of 400 Angus × Hereford heifers originating from Montana were used to determine the effects on performance when intake of a high-energy corn by-product-based diet is increased to near ad libitum intake. The Bottom Line:One high-energy diet based on wet corn gluten feed can be offered to achieve a variety of gains efficiently by only altering the amount of feed offered.
Keywords: Stocker cattle; limit-feeding